A case of intraductal tubulopapillary neoplasm of the pancreas in a branch duct: a rare case report and literature review - Atsushi Yamaguchi; Takuro Hamada; Kaoru Wada; Riho Moriuchi; Kanae Tao; Hirona Konishi; Yuzuru Tamaru; Ryusaku Kusunoki; Toshio Kuwai; Hirotaka Kouno; Kohei Ishiyama; Naoto Hadano; et al. (BMC Gastroenterology, 2021)
Abstract Background Intraductal tubulopapillary neoplasm (ITPN) of the pancreas is a new disease concept defined by the World Health Organization in 2010. ITPN progresses with tubulopapillary growth in the pancreatic duct and is known to have a fair prognosis. Localization in the main pancreatic duct (MPD) is one characteristic. There are few case reports of ITPN in a branch of the pancreatic duct (BD). Case presentation We encountered a case of ITPN localized in BD. An 85-year-old man was followed after colonic surgery for rectal carcinoma. An abdominal computed tomography scan revealed a cystic mass in the pancreatic head and further examination was done. A T2 weighted intension picture in magnetic resonance imaging showed a 20 mm cystic lesion with an internal mass of 15 mm. Duodenal papilla were slightly open and endoscopic retrograde pancreatography revealed mild and diffuse dilatation of the main pancreatic duct and mucin in the MPD. In consideration with the image examinations, we diagnosed the tumor as an intraductal papillary mucinous neoplasm with carcinoma because of its large mural nodule (> 10 mm in size) in a cyst. Consequently, a pancreaticoduodenectomy was performed. Macroscopically, a white solid tumor sized 2.5 × 1.8 × 1.0 was identified in the head of the pancreas. The cut surface of the resected pancreas showed a side-branch type intraductal tumor with tubulopapillary architecture without mucin secretion. Immunohistochemical staining was positive for MUC1, and negative for MUC2 and MUC5AC. The final diagnosis was determined to be pancreatic ITPN from BD. At the time of this report (48 months post-surgery), the patient remains disease-free without evidence of recurrence. Conclusion ITPNs localized in BD are rare and diagnosis prior to surgery is difficult. In our case, the shape was round, not papillary, and with little fluid. These characteristics are different from a branch duct type IPMN and can be a clue to suspect ITPN in BD.